Chemical composition of organic compost drived from oil palm biomass wastes - Rozelyn Ignesia Raymond; Januarius Gobilik; Chong, Khim Phin (American Institute of Physics Inc., 2024)
Palm oil export in Malaysia has contribute significantly to the economic of the country yet the large production of the underutilized oil palm wastes such as empty fruit bunches (EFB), oil palm decanter cake (OPDC), oil palm leaves and fronds (OPLF), palm pressed fibers (PPF), and palm oil mill effluent (POME) accounts for a significant share of environmental problems. One of the alternatives to reduce these wastes is by composting the oil palm waste materials simultaneously into some value-added product for plant growth. This study was conducted to investigate the nutrient composition of organic compost made up from shredded EFB, OPDC, OPPF, OPLF, and POME in three different ratio consisting of compost 1 (C1) 1:2:1:1:1, compost 2 (C2) 2:1:1:1:1, and compost 3 (C3) 2:2:1:1:1. Weekly mixing of the composting materials was conducted up to 120 days where the pH of compost increased from acidic to alkaline for each compost combination. The C/N ratio of each compost combination increased significantly while the nutrient composition of nitrogen (N), phosphorus (P), potassium (K), magnesium (Mg) and sulphur (S) also significantly increased. The compost combination (1:2:1:1:1) was found to be the most ideal compared to the other combinations with C/N ratio of 13.07, pH 7.6, and nutrient composition N (3.03%), P (0.37%), K (2.31%), Mg (0.61%) and S (0.86%). This study examines the potential of palm oil wastes that could be developed into organic compost that helps in promoting plant growth.